2015
DOI: 10.1111/maec.12259
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term spatial dynamics in vegetated seascapes: fragmentation and habitat loss in a human‐impacted subtropical lagoon

Abstract: Vegetated coastal seascapes exhibit dynamic spatial patterning, some of which is directly linked to human coastal activities. Human activities (e.g. coastal development) have modified freshwater flow to marine environments, resulting in significant changes to submerged aquatic vegetation (SAV) communities. Yet, very little is known about the spatially complex process of SAV habitat loss and fragmentation that affects ecosystem function. Using habitat mapping from aerial photography spanning 71 years for Bisca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 74 publications
1
37
0
Order By: Relevance
“…Associations between nearshore pink shrimp abundance and depth have been previously reported [75,80,94,95]. Other studies that focused on very nearshore areas (<100 m) also found higher abundances there [8–10,12,96]. Recruiting postlarval pink shrimp often concentrate in SAV near the low-tide mark along shorelines [9,12,97–102].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Associations between nearshore pink shrimp abundance and depth have been previously reported [75,80,94,95]. Other studies that focused on very nearshore areas (<100 m) also found higher abundances there [8–10,12,96]. Recruiting postlarval pink shrimp often concentrate in SAV near the low-tide mark along shorelines [9,12,97–102].…”
Section: Discussionmentioning
confidence: 79%
“…The seemingly weak statistical relationships with either total or species-specific SAV metrics was unexpected. Pink shrimp associations with H. wrightii have been previously reported [12,96,97,106], while other studies have reported maximal pink shrimp densities relative to total SAV biomass or % cover [10,107,108]. Although one study reports negative impacts of drift and attached algal biomass [109], the positive relationships reported by most studies suggested a stronger relationship between pink shrimp density and either species-specific or total SAV would be readily observed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…, Santos et al. ). Therefore, nutrient and sediment loading rates, to a great extent, determine bed resilience to multiple stressors.…”
Section: How Is the Tmdl Likely To Change These Measures Of Resilience?mentioning
confidence: 99%
“…High nutrient loads limit the light available for photosynthesis, which decreases available energy stores and makes plants more susceptible to dying during light-limiting disturbances such as turbidity pulses during storm events (Moore et al 1997, Longstaff and Dennison 1999, Yaakub et al 2014. Under these conditions, SAV cover becomes increasingly fragmented, reducing the capacity for feedbacks that enhance habitat conditions (Montefalcone et al 2010, Santos et al 2016). Therefore, nutrient and sediment loading rates, to a great extent, determine bed resilience to multiple stressors.…”
Section: How Is the Tmdl Likely To Change These Measures Of Resilience?mentioning
confidence: 99%